USE OF INTERACTIVE METHODS IN MATHEMATICS LESSONS - Alijonov Sirojiddin Husan oʻgʻli; Khabibullaev Sherozbek Khamidulla o'g'li; Tokhtaev Zakirjon Abidovich; Usmonov Isroiljon Muxtorjon o'g'li (American Journals, 2023)
This article discusses the use of interactive methods in mathematics classes. Another benefit of using interactive methods in mathematics classes is that they provide versatility in teaching methods.
Keywords: Problem, interactive methods, thinking, Mathematical, individual, games.